The effect of anaesthesia and antenatal care on feto-maternal outcome after caesarean section in a developing country - Onyekwulu, Fidelis A.; Okonna, Friday G.; Okeke, Tochukwu C.; Okwor, Israel O. (International Journal of Research in Medical Sciences, 2020)
Background: The feto-maternal outcome after delivery is precarious in developing country. The anaesthetic technique and antenatal care as it affect this outcome is assessed. Methods: This is a 5-year retrospective study carried out at the University of Nigeria Teaching Hospital Enugu. Obstetric theatre records of patients who had caesarean section between January 1st 2011 and December 31st 2015 were reviewed. Data extracted from the records using a proformer included socio-dermographic characteristics, indications for surgery, maternal and neonatal outcome, and anaesthetic technique. The data were analyzed using SPSS Version 17 [SPSS Inc., Chicago, IL, USA]. Results: A total of 1574 patients had caesarean section within the study period and 1158 (73.6%) of the patients were booked, while 416 (26.4%) were unbooked. The total number of deliveries during this period was 6235 giving a caesarean section rate of 39.6%. More deaths on the operating table were recorded in the unbooked patients as compared to booked parturient (x2=20.013, p<0.001). More babies of the unbooked patients died perioperatively (17.3%) when compared to booked paturient (3.4%) p<0.001. Conclusions: The commonest anaesthesia administered was subarachnoid block. Maternal and neonatal mortality was significantly higher in paturient who did not attend antenatal care compared to those who attended.